2021
DOI: 10.1002/arch.21763
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function analysis of PGRP‐S1 from the oriental armyworm, Mythimna separata

Abstract: Peptidoglycan recognition proteins (PGRPs) are well known for their abilities to recognize or hydrolyze peptidoglycan (PGN), one of the major bacterial cell wall components. However, much less is known about their antifungal activities. PGRP‐S1 was previously identified from a crop pest, Mythimna separata (Walker) (Lepidoptera: Noctuidae). PGRP‐S1 showed bacteriolytic activities against Gram‐positive and Gram‐negative bacteria. In this study, tissue expression analysis showed that PGRP‐S1 was mainly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…We predicted that both genes belong to the short form of PGRP, which is a secreted extracellular protein. For most PGRPs that have amidase activity, this activity is contained in the H–Y–H–T–C structure [ 25 ]. Sequence comparison showed that in the OfPGRP-A sequence, tyrosine is mutated to serine and cysteine is mutated to serine, suggesting that OfPGRP-A lacks amidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that both genes belong to the short form of PGRP, which is a secreted extracellular protein. For most PGRPs that have amidase activity, this activity is contained in the H–Y–H–T–C structure [ 25 ]. Sequence comparison showed that in the OfPGRP-A sequence, tyrosine is mutated to serine and cysteine is mutated to serine, suggesting that OfPGRP-A lacks amidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the molecular interactions between entomopathogens and insects may help to develop new strategies for pest management [ 24 ]. Although a few immune factors in M. separata have been identified, less is known about its CTL family [ 25 , 26 , 27 ]. This study aims to construct a transcriptome of M. separata larvae and identify CTLs.…”
Section: Introductionmentioning
confidence: 99%